A trajetória cultural de Flamínio Fávero e suas contribuições socioeducacionais - Oliveira, Mariana Matos (2019)
The present work has as objective to deal with the cultural trajectory of Flamínio Fávero and his socioeducational aids. This relicate personalisable historietalized images is used here "cultural biography", with a vial retired and plots social, for the viviented in its historical-cultural context, taking its own trajetory with several influences that focused on this scenario. His identity, under his domain, his profile, his profile, his flow of his own identity is clearly See from his speeches and texts, besides the repercussions of oversizing in the Brazilian sociopolitical context of the time. It is not, therefore, a purely descriptive approach, but so that the biography can be presented through texts, images, documents and documents that speak about themselves and leave traces of their trajectory. The work shows the understanding of the role of the intellectual elite in the context in which it is inserted, referring to the network of belonging to Flaminio Fávero and mapping the foundations of his engagement in this group. Secondary education, specialization in secondary education, the formation of higher education in relation to its journey was closely linked, as well as the balance of socio-educational support, its merit, importance and prominence.